Hubungan antara Paradigma Lingkungan Baru (New Environmental Paradigm) dan Niat untuk Bertindak (Intention to Act) dengan Perilaku Tanggung Jawab Lingkungan (Responsible Environmental Behavior) Siswa - Khairunnisa Salsabila; I Made Putrawan; Diana Vivanti Sigit (IJEEM - Indonesian Journal of Environmental Education and Management, 2021)
To avoid environmental damage continuously, is important to construct a responsible environmental behavior early on. The things that contribute to one’s behavior towards environment are the paradigm and intention to improve the environment. Therefore, this study aims to know the relation between new environmental paradigm and intention to act with students responsible environmental behavior. The study was carried out in SMA Negeri 36 Jakarta in October-December 2019 by involving as many as 97 samples of students. The method used is descriptive method with a correlational study approach using simple and multiple correlation regression analysis. The results of the study revealed that there was a positive and significant relationship between the new environmental paradigm of students with responsible environmental behavior; there was a positive and significant relationship between the intention to act of students with responsible environmental behavior; and there is no relation between new environmental paradigm and intention to act of students together with responsible environmental behavior. Responsible environmental behavior variations on students SMA Negeri 36 Jakarta amounting to 2% are determined jointly by the new environmental paradigm and 36.6% by the intention to act. Therefore, in increasing the responsible environmental behavior of students to be more positive, need to consider factors new environmental paradigm and intention to act of students who contribute significantly.